Innovative Mindset in School Education: Aglobal issue or trend in Pakistan? - Hamid, Syeda Saira (European Scientific Journal, ESJ, 2017)
Education and training are emerging now key drivers of competitiveness for any country on the globe. To cope with the globalization a country has to elevate her education system. In Pakistan HEC upgraded the Teacher Education (TE) by replacing the one year B.Ed. with the 4 year B.Ed (Honors) recently. The upgraded TE and the global challenges are well connected with the real implementation of vision 2030 agenda in the School Education (SE). And crucial to address the advancements in TE for the production of teachers with innovative mindset to grip the global reach in the future. The Punjab government is planning to stop the upgraded 4-year program offered since 2009 in the 33 Government Elementary Colleges for Teachers Training (GCETs) instead of making the GCETs self sustain. The study with the mixed methods of research visualized the advanced professional training needs and essential global demands data from the 33 GCETs including 33 (100%) principals, 330 (82%) teacher- educators and 200 (66.6%) prospective- teachers. Then it strived to propose a transformation mechanism for the elevation of TE. The data analyzed quantitatively by frequencies, percentages and qualitatively through focused group discussions, triangulation and content analysis. Study designed to resolve the globalization issue, by bridging the gaps through a transformation framework for modification in TE. The conceived factual framework is a dynamic revolutionary route to improving the quality of school education via contemporary TE. The suggested framework if implemented would save the scarce resources and provide maximum outputs through quality education.